Bighorn Sheep Genetic Structure in Wyoming Reflects Geography and Management. Issue 6 (29th May 2020) - Love Stowell, Sierra M.; Gagne, Roderick B.; McWhirter, Doug; Edwards, William; Ernest, Holly B.
ABSTRACT: Aligning wildlife management boundaries with accurate biological units promotes effective conservation and management practices that reflect ecological and evolutionary processes. Neutral genetic markers allow for quantitative delineation of population structure without a priori assumptions or biases. In the United States, bighorn sheep ( Ovis canadensis ) are a charismatic component of Wyoming's biodiversity and a species that provides important viewing and hunting opportunities. Bighorn sheep abundances are relatively stable throughout Wyoming, and the species is managed by administrative units identified using expert knowledge, distribution and movement data, and geographic and administrative boundaries. We used a panel of 38 variable microsatellite loci and 512 base pairs of mitochondrial DNA sequence to identify the genetic structure throughout the state and in translocation source herds, quantify the extent of genetic diversity within each genetic cluster, and estimate the degree of gene flow among herds using blood and tissue samples collected 1989–2017. We identified genetic structure of Rocky Mountain bighorn sheep in the major mountain ranges of Wyoming, with strong support for ≥5 genetic clusters using microsatellite loci. These genetic clusters generally aligned with current management units, whereas mitochondrial data showed a more complex mosaic that was not geographically patterned. Genetic variation estimated from both markers was high within each herd and comparable among herds. The assignment of individuals reflected a combination of geographic isolation and translocation, which has been extensive. Our results provide a state‐wide assessment of genetic diversity and structure that will enhance management by understanding the outcomes of translocation, identifying the source of unknown individuals, and parameterizing disease ecology models. © 2020 The Wildlife Society. Abstract : Population genetic analyses of bighorn sheep in Wyoming, USA, 2012–2017 identified genetic clusters that reflect biogeographic and management history. Concern for maintaining genetic connectivity should be balanced against the potential for disease transmission.